PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA PADA TEMA DAERAH TEMPAT TINGGALKU KELAS IV SD NEGERI 050600 KUALA TAHUN PEMBELAJARAN 2018/2019 - Sitanggang, Dornani Defiana Br. (Jurnal Ilmiah Aquinas, 2019)
The problem in this study is that student learning outcomes are still low on the theme of the area where I live in class IV 050600 Kuala State Elementary School. The purpose of this study was to determine the effect of the Quantum Teaching learning model on student learning outcomes on the theme of the area where I live in class IV 050600 Kuala State Elementary School the learning year 2018/2019. This type of research is a quantitative research experimental model with a pretest-posttest Control Group Design research design. The class that becomes the population in this study is class IV-A and class IV B, where the population is 39 students with class IV A 18 students, and class IV B 21 students. Sampling uses a simple random sampling technique, and class IV B is selected as a class given treatment. To find out the hypothesis in this study using a different test independent sample t-test in SPSS ver 22.The results showed that the experimental class experienced a learning increase of 42% from the previous pretest. In the experimental class the pretest results were 58.85 and posttest was 83.61. This is supported by the results of testing the correlation coefficient. It can be seen that the correlation coefficient value is 0.772, which means that it is calculated (0.772) > rtable (0.433) then Ha is accepted. Then there is a strong relationship and there is an influence the Quantum Teaching model on learning outcomes in class IV 050600 Kuala State Elementary School. Can also be seen from the results of testing the hypothesis t-test where tcount> ttable is 33,035> 1,687 so that the hypothesis Ha is accepted. This shows the influence of the Quantum Teaching learning model on student learning outcomes on the theme of the area where I live in class IV 050600 Kuala State Elementary School in the 2018/2019 learning year.